A longitudinal study investigating bidirectionality among nonsuicidal self-injury, self-criticism, and parental criticism. (January 2019) - Daly, Owen; Willoughby, Teena
Highlights: Nonsuicidal self-injury predicts greater self-criticism over time. Higher self-criticism does not predict nonsuicidal self-injury over time. Maternal and paternal criticism are not associated with NSSI engagement over time. Abstract: Previous research has indicated that both self-criticism and parental criticism may be associated with engagement in nonsuicidal self-injury (NSSI). However, much less is known about the temporal sequencing of these relationships (i.e., do self-criticism and parental criticism predict NSSI across time, or does NSSI predict self-criticism and parental criticism across time?). Undergraduate students ( N  = 1132; 70.5% female; M age  = 19.06) from a midsized Canadian university completed measures of NSSI, self-criticism, maternal criticism, and paternal criticism at two time points (one year apart). An autoregressive cross-lagged path analysis revealed that there was a significant unidirectional relationship between NSSI and self-criticism, such that greater NSSI frequency predicted greater self-criticism across time, but self-criticism did not predict greater NSSI frequency across time. In addition, both maternal and paternal criticism were not significantly associated with NSSI frequency when examining either direction of effects. Overall, our results challenge the notion that self-criticism is a risk factor for NSSI engagement, and instead, suggest that it may be a consequence of NSSI engagement. Intervention programs may benefit from recognizing that individuals who engage in NSSI may subsequently criticize themselves.